2013
DOI: 10.1093/ndt/gft260
|View full text |Cite
|
Sign up to set email alerts
|

Predicting mortality in haemodialysis patients: a comparison between lung ultrasonography, bioimpedance data and echocardiography parameters

Abstract: To our knowledge, this study is the first one that compares three different strategies to predict mortality in haemodialysed patients. The lung comet score emerged as the best predictor for the relationship hydration status-mortality, independently of bioimpedance-derived parameters in this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

22
125
4

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 103 publications
(151 citation statements)
references
References 19 publications
22
125
4
Order By: Relevance
“…Comparing the studies of Mallamaci et al 16 and Siriopol et al, 4 we observe that cardiac function correlates with lung water only in the former. We suppose that the divergence related to the correlation between cardiac function, and lung congestion is partially explained by sample characteristics.…”
Section: Resultssupporting
confidence: 55%
See 3 more Smart Citations
“…Comparing the studies of Mallamaci et al 16 and Siriopol et al, 4 we observe that cardiac function correlates with lung water only in the former. We suppose that the divergence related to the correlation between cardiac function, and lung congestion is partially explained by sample characteristics.…”
Section: Resultssupporting
confidence: 55%
“…In the multivariate analysis, only the IVC collapse index (b = 45.038; p < 0.001) and NYHA classes (b = 13.995; p = 0.006) were independent predictors of the number of B lines (Table 5). 4,15 we showed the lack of association between lung congestion and hydration status, as assessed by bioimpedance. This result leads to practical implications, since extracellular water assessed by bioimpedance is usually the guide for the ultra--filtration prescription of HD patients.…”
Section: Resultsmentioning
confidence: 79%
See 2 more Smart Citations
“…Finally, the authors conclude that there are currently no studies in the literature reporting statistically significant data on the accuracy of US imaging in the assessment of hydration status in uremic patients: however, there have been several studies published about the usefulness of ultrasound of the lung and echocardiographic parameters in this setting [9][10][11][12][13][14]. While some studies have found that lung B-lines are strongly influenced by left ventricular function [15], our group confirmed correlation of lung ultrasound with hydration status also in well compensated hemodialysis patients [7].…”
mentioning
confidence: 97%